How Do Auditors View Manager's Voluntary Disclosure Strategy? The Effect of Earnings Guidance on Audit Fees - Krishnan, Gopal V; Pevzner, Mikhail; Sengupta, Partha (Elsevier, 2011)
The objective of this study is to examine the relation between attributes of earnings forecasts issued by managers and audit fees. Although there is an extensive literature on managers’ disclosure of earnings forecasts, there is a paucity of research on how auditors incorporate information from these voluntary disclosures. We find that the issuance of an annual or quarterly management earnings forecast in the prior period is positively associated with the current period audit fees. Our results indicate that on average, audit fees are higher by about 7% for firm-years associated with an annual forecast. Among the firms that issue earnings forecasts, we find no association between audit fees and likelihood of updating a previously issued earnings forecast, indicating that auditors do not view such behavior negatively. Further, we find audit fees to be positively associated with the error and the bias (or optimism) in the forecasts for annual forecasts but not for quarterly forecasts. Overall, these results suggest that management’s forecast behavior captures higher business risk for the auditor via greater risk of earnings management or litigation risk.
Keywords: Audit fees; Management Earnings forecasts; Litigation Risk; Fraud Risk